Dialectical Linguistics of Public Signs in Sidoarjo Regency: An Approach in Ecolinguistics Study - Ferina Kumala Dewi (Universitas Nahdlatul Ulama Blitar, 2020)
This study aims to reveal the ideological, sociological and biological background of the public signs. This study is focused on public sign in Sidoarjo Regency. In this case, I collected data in several public areas namely International airport, bus station, train station, housing, school, park, and cemetery on 18 subdistricts in Sidoarjo regency in 2019. In total, there are 65 data, which are taken purposively to show ideological, sociological, and biological dimension. There are three conclusions in this study. First, in Biological background, several morphemes that reflected biological condition in either biotic or abiotic components are found in aquaculture area, park, cemetery and housing. Second, the ideological background, the public sign that contained belief, myth, and paradigm in a society are found in housing, train station, park, river, gas station, cemetery, mosque and factory. Third, in sociological dimension, the morphemes and phrases contain various job, political system, status and economy in a society in Sidoarjo Regency.